Is R & D risky? - Bromiley, Philip; Rau, Devaki; Zhang, Yu (Strategic Management Journal, 2017)
Research summary : Many studies use research and development ( R & D) intensity or R & D spending as a proxy for risk taking, but we have little evidence that either associates positively with firm risk. We analyze the relations between R & D intensity ( R & D spending to sales) and R & D spending on the one hand and 11 different indicators of firm risk on the other, using data from 1,907 to 3,908 firms in various industries over 13 years. The analysis finds a general lack of consistent positive association between R & D and firm risk, making the use of R & D as an indicator of risk taking questionable. Furthermore, R & D intensity and spending do not correlate positively, suggesting they measure different constructs. We discuss potential reasons for these nonsignificant results. Our study demonstrates that researchers should avoid casual use of R & D as a proxy for risk taking without explicitly providing a clear definition and measurement model for risk . Managerial summary : Risk is a key construct in strategic management research. Many studies in this area measure risk taking by research and development ( R & D) intensity (the ratio of R & D spending to sales) or R & D spending. However, since R & D intensity and spending have also been used to measure various other things such as information processing demands, this raises the question of whether R & D intensity and spending are valid indicators of firm risk. We examine this issue by considering the associations of R & D intensity and R & D spending with conventional measures of firm risk. We find a general lack of consistent positive association between R & D and firm risk, making the use of R & D as an indicator of risk taking questionable. Furthermore, R & D intensity and spending do not correlate positively, suggesting they measure different things . Copyright © 2016 John Wiley & Sons, Ltd.